Effect of silica nanofiller in cross-linked polyethylene as electrical tree growth inhibitor - Moh Nazar, Nazatul Shiema; Syazwani Mansor, Noor; Khayam, Umar; Asiah Muhamad, Nor; Jaafar Mustapha, Mariatti; Izzani Mohamed, Amir; Mohd Jamil, Mohamad Kamarol (International Journal of Electrical and Computer Engineering (IJECE), 2022)
One of the main phenomena that contributes to the non-success of cable insulation made of cross-linked polyethylene (XLPE) is electrical treeing. To improve the XPLE cable insulation, the use of nanofiller has been introduced. Adding the nanofiller in the based composite offers better cable lifetime and resistance to deal with the cable failure. One of the potential nanofillers that can increase the insulation performance of XLPE cable is silica nanofiller. To this extent, the studies on silica nanofiller in XLPE are focusing on the impulse breakdown strength, dielectric loss, permittivity, space charge, alternating current (AC), and partial discharge. The studies reveal that the dielectric properties of the XLPE nanocomposite have significant improvement. Therefore, this work investigates the effect of various concentrations of silica nanofiller in XLPE composite as electrical tree inhibitor. The concentrations of silica nanofiller in XLPE were 0.25 wt%, 0.5 wt%, 0.75 wt%, 1.0 wt%, 1.25 wt%, 1.5 wt%, and 1.75 wt%. The silica nanofillers have 96%-99% purity, 20-30 nm sizes and the shapes are spherical. As a result, the XLPE composite containing 1.5 wt% silica nanofiller demonstrate higher tree inception voltage and detaining the tree propagation speed, which could be considered as an inhibitor medium of electrical tree growth.